Enhancing high-order harmonic generation by controlling the diffusion of the electron wave packet - Severt, T.; Troß, J.; Kolliopoulos, G.; Ben-Itzhak, I.; Trallero-Herrero, C. A. (My University, 2021)
We experimentally study the enhancement of high-order harmonic generation (HHG) driven by synthesized ω−3ω laser fields, where we control whether the ionization rate or the electron wave packet’s diffusion is the dominant enhancement mechanism. When minimizing the electron wave packet’s diffusion, the excursion times of the corresponding electron trajectories are reduced by a factor of 2 or more. This result is important for imaging techniques that use the returning electron wave packet to probe the remaining ion. Furthermore, we achieve a 10× to 3800× enhancement of the harmonic yield driven by the bichromatic fields relative to that of an optimized single-color field, showing that the bichromatic fields improve HHG’s capability as a light source. We also measure that the two-color field’s harmonics have half the divergence angle compared to their single-color counterpart, suggesting that the “short” electron trajectories play a more prominent role compared to their “long” trajectory counterparts, thus improving the wavefront of the emerging harmonic beam.